Negative family upbringing patterns and their impact on academic achievement among second year students in the city of Sharjah: A descriptive study - Alneaimi, Naji; Al-Halalat, Khalil (Al-Adab Journal, 2025)
The current study aimed to identify the impact of negative family upbringing and its relationship with academic achievement among second cycle students in schools in the Emirate of Sharjah, by identifying the negative family upbringing patterns prevailing in the Emirate of Sharjah, and the most important social variables affecting the family upbringing patterns used, in addition to identifying the most negative family upbringing pattern on the academic achievement of children from parents. The study used the descriptive-analytical method to analyze the data, and relied on a purposive sample consisting of (100) male and female students from second cycle schools in the Emirate of Sharjah, and (50) parents. The study used a questionnaire to collect data. One of the most important findings that emerged from the current study is the agreement of the sample members, who represent about half of the sample size, that the ranking of fathers' practices of negative socialization methods from high to low:  Cruelty and authoritarianism, oscillation, segregation, rejection and neglect, triggering psychological pain, overprotection, and finally pampering and indulgence. While the results showed that mothers' practices of negative socialization methods were ranked from high to low: Overprotection, ostracism, neglect, oscillation, segregation, cruelty, authoritarianism, overprotection and finally pampering and indulgence, which have a negative relationship with children's academic achievement. The study came up with the most important recommendations: Agreement in the parenting style between fathers and mothers in a balanced manner would produce a generation that is emotionally, psychologically and educationally balanced. The study also recommends that parents educate themselves on positive parenting techniques by taking advantage of the programs offered by family development institutions and other centers.